2010
DOI: 10.25011/cim.v33i6.14593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of montelukast on burn wound healing in a rat model

Abstract: Purpose: Montelukast, a selective cysteinyl leukotriene D4-receptor antagonist, is used in the treatment of asthma. In a rat model, our aim was to investigate the effects of montelukast, alone or in combination with topical antibiotics, on local burn wound healing. Methods: Rats were randomly allocated to four groups after local burn development: Group 1; rats were left to secondary healing without treatment, Group 2; a dose of 10 mg/kg montelukast was given by gastric gavage once a day for 10 days, Group 3;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…It is reported that montelukast can reduce eosinophilic inflammation in the airways [3537]. Besides CysLT 1 receptor antagonists or biosynthesis inhibitors ameliorate at ethanol-induced gastric mucosal damage [38] and wound healing [39, 40]. According to our results, montelukast treatment after Mtx injection reduced the MDA and MPO levels.…”
Section: Discussionsupporting
confidence: 66%
“…It is reported that montelukast can reduce eosinophilic inflammation in the airways [3537]. Besides CysLT 1 receptor antagonists or biosynthesis inhibitors ameliorate at ethanol-induced gastric mucosal damage [38] and wound healing [39, 40]. According to our results, montelukast treatment after Mtx injection reduced the MDA and MPO levels.…”
Section: Discussionsupporting
confidence: 66%
“…[34][35][36] Besides, CysLT1 receptor antagonists or biosynthesis inhibitors ameliorate ethanol-induced gastric mucosal damage, 37,38 experimental colitis, 39 and wound healing. 22,40,41 Recently, Sener et al 16 have reported that montelukast has protective effects on chronic renal failure-induced multiple organ injury. They attributed this to montelukast's ability to inhibit neutrophil infiltration and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because of its oily and moisturizing features, topical antibiotics are required to promoting burn wound healing and re-epithelialisation 11 . Topical antimicrobial agents containing silver sulfadiazine have been used clinically to eliminate infections common in local burn wounds 12 . Therefore we compared treatment with OP pomade with no treatment and topical treatment alone.…”
Section: Discussionmentioning
confidence: 99%